Lethal Effects of Aspergillus niger against Mosquitoes Vector of Filaria, Malaria, and Dengue: A Liquid Mycoadulticide - Gavendra Singh; Soam Prakash (The Scientific World Journal)
Aspergillus niger is a fungus of the genus Aspergillus. It has caused a disease called black mold on certain fruits and vegetables. The culture filtrates released from the A. niger ATCC 66566 were grown in Czapek dox broth (CDB) then filtered with flash chromatograph and were used for the bioassay after a growth of thirty days. The result demonstrated these mortalities with LC50, LC90, and LC99 values of Culex quinquefasciatus 0.76, 3.06, and 4.75, Anopheles stephensi 1.43, 3.2, and 3.86, and Aedes aegypti 1.43, 2.2, and 4.1 μl/cm2, after exposure of seven hours. We have calculated significant LT90 values of Cx. quinquefasciatus 4.5, An. stephensi 3.54, and Ae. aegypti 6.0 hrs, respectively. This liquid spray of fungal culture isolate of A. niger can reduce malaria, dengue, and filarial transmission. These results significantly support broadening the current vector control paradigm beyond chemical adulticides.